Bulaklak ng Maynila. (Quezon City : VIVA VIDEO, 2000)
It's a world where crimes is commonplace but money is scarce. It's a place where the strong is king and the weak is prey. Welcome to Ada's (Angelu de Leon) world. The daughter of impoverished parents, Ada's life becomes even more miserable when her father, Roque (Bembol Rocco), is imprisoned after attempting to rob bank. For them to survive, Azun (Elizabeth Oropesa), Ada's mother, gives in to Timo's (Christopher de Leon) offer that they live with him. A heartless usurer, Timo rapes Ada. Azun turns a deaf ear to Ada's complaint, and she instead accuses her being an ingrate. Forsaken by her own mother, Ada leaves home and becomes a sexy dancer to survive...